A new species of Microglanis Eigenmann, 1912 (Siluriformes, Pseudopimelodidae) from rio São Francisco basin, Brazil - Mori, Horácio; Shibatta, Oscar A. (Zootaxa, 2006)
Microglanis leptostriatus n. sp. is described from the middle-upper rio São Francisco basin. The new species is distinguished from its congeners by the following combination of characters: light transverse stripe, located in occipital region between the opercular openings, thin and sinuous; pale region below dorsal and adipose fins mottled with brown spots; and a dark stripe in the axis of gill filaments in alcohol preserved specimens. Microglanis leptostriatus is further distinguished from M. parahybae and M. garavelloi, the closest species geographically, by having the following combination of characters: longer head length [28.3–32.1% of SL (mean = 30.0) versus 25.5–28.5% (mean = 27.2) and 25.2–30.2 (mean = 28.0), respectively], shorter dorsal spine length [11.7–14.9% of SL (mean = 13.6) versus 14.1–18.1% (mean = 16.0) and 11.3–19.0 (mean = 15.5)], shorter pectoral spine length [12.5–19.7% of SL (mean = 17.4) versus 19.4–22.7% (mean = 20.6) and 18.5–26.2 (mean = 22.1)].